Broken Dreams : an Intimate History of the Midlife Crisis - Jackson, Mark (Reaktion Books, 2021)
The midlife crisis has become a cliché in modern society. Since the mid-twentieth century, the term has been used to explain infidelity in middle-aged men, disillusionment with personal achievements, the pain and sadness associated with separation and divorce, and the fear of approaching death. This book provides a meticulously researched account of the social and cultural conditions in which middle-aged men and women began to reevaluate their hopes and dreams, reassess their relationships, and seek new forms of identity and fresh pathways to self-satisfaction. Drawing on a rich seam of literary, medical, media, and cinematic sources, as well as personal accounts, Broken Dreams explores how the crises of middle-aged men and women were shaped by increased life expectancy, changing family structures, shifting patterns of work, and the rise of individualism.